2007
DOI: 10.1179/136485907x154566
|View full text |Cite
|
Sign up to set email alerts
|

Doppler ultrasonography reveals adult-worm nests in the lymph vessels of children with brugian filariasis

Abstract: Although ultrasonography has allowed 'nests' of live adult worms and dilated lymphatics to be detected in the early stages of infection with Wuchereria bancrofti, previous attempts to locate such adult-worm nests in brugian filariasis have been unsuccessful. In this study, the successful location of live adult Brugia malayi parasites, in the lymphatics of the axilla, thigh, epitrochlear region and/or popliteal fossa of children aged 3-15 years, is described for the first time. The 'filarial dance sign' (FDS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…In this population, it was found on screening that, while the prevalence of microfilaraemia by blood-smear examination was only 0·38%, the BR test was positive in 10·97%. Similar to what is seen by ICT card testing in bancroftian filariasis, the BR test thus identified nearly 27 times more 'infected' individuals in Brugia malayi infection than the conventional mf detection by blood smear examination (Shenoy et al 2007a(Shenoy et al , 2009). From the above group, 100 children were enrolled for the chemotherapy studies, out of which 77 tested positive for filaria-specific IgG4 antibody.…”
Section: Immuno-diagnosis Of Lf Infection In Childhoodsupporting
confidence: 69%
“…In this population, it was found on screening that, while the prevalence of microfilaraemia by blood-smear examination was only 0·38%, the BR test was positive in 10·97%. Similar to what is seen by ICT card testing in bancroftian filariasis, the BR test thus identified nearly 27 times more 'infected' individuals in Brugia malayi infection than the conventional mf detection by blood smear examination (Shenoy et al 2007a(Shenoy et al , 2009). From the above group, 100 children were enrolled for the chemotherapy studies, out of which 77 tested positive for filaria-specific IgG4 antibody.…”
Section: Immuno-diagnosis Of Lf Infection In Childhoodsupporting
confidence: 69%
“…Infection often occurs in childhood but the obvious clinical effects of the disease such as filarial lymphedema or hydrocele may not occur until they reach adolescence [4]. Shenoy et al [5], [6] have shown covert abnormalities in the lymphatics with lymphoscintigraphy and worm nests by Doppler ultrasonography in B.malayi LF-infected adolescents as young as three years. Importantly, it has also been shown that these early lymphatic changes can be reversed by rug administration [7].…”
Section: Introductionmentioning
confidence: 99%
“…This has also been confirmed by prevalence studies on microfilaremia and filarial antigenemia in children [34,35]. Existence of live adult filarial worms has been shown on Doppler sonography and lymphatic dilatation by lymphoscintigraphy in children aged 3-15 yr [13,15]. This lymphatic pathology in infected children, since it is known to persist, might pave way for future development of disease manifestations.…”
Section: Filarial Disease Manifestations In Childrenmentioning
confidence: 58%
“…Other common locations described in women and children are larger lymph vessels and lymph nodes draining to lower and upper limbs [11,12]. In brugian filariasis also adult worms were detected by Doppler sonography in the lymphatics of the inguinal and axillary regions in children [13]. The adult parasites live in these sites for 6-8 yr or more and are responsible for initiating the early pathology in LF.…”
Section: Introductionmentioning
confidence: 99%